Transport and Permeation Properties of Dapivirine: Understanding Potential Drug-Drug Interactions - Ruohui Zheng; Guru R. Valicherla; Junmei Zhang; Jeremy Nuttall; Peter Silvera; Leslie J. Marshall; Philip E. Empey; Lisa C. Rohan (MDPI AG, 2022)
The dapivirine (DPV) vaginal ring was developed by the nonprofit International Partnership for Microbicides (IPM) for reducing the risk of HIV infection. A clinical study (IPM 028) showed that concomitant use of the DPV ring and miconazole (MIC) altered DPV pharmacokinetic profile. In this work, we investigated whether or not DPV transport and permeation contributed to the observed DPV-MIC interaction. Our study evaluated the interaction between DPV and several transporters that are highly expressed in the human female reproductive tract, including MRP1, MRP4, P-gp, BCRP, and ENT1, using vesicular and cellular systems. We also evaluated the impact of DPV/MIC on cellular tight junctions by monitoring transepithelial electrical resistance with the Ussing chamber. Lastly, we evaluated the effect of MIC on DPV permeability across human cervical tissue. Our findings showed that DPV was not a substrate of MRP1, MRP4, P-gp, BCRP, or ENT1 transporters. Additionally, DPV did not inhibit the activity of these transporters. DPV, MIC, and their combination also did not disrupt cellular tight junctions. MIC did not affect DPV tissue permeability but significantly reduced DPV tissue levels. Therefore, our results suggest that the DPV-MIC interaction is not due to these five transporters, altered tight junction integrity, or altered tissue permeability.